Photographic Feature in the Short Story Written for Children in Iraq A Theoretical Reading and an Applied Study in the Stories of the Third Millennium - Faisal, Anahed Naji; Alharthi, Jokha Mohammed (Dirasat: Human and Social Sciences, 2024)
Objectives: draw attention to a new topic, which is the photographic feature in the short stories written for children in Iraq in the third millennium.. The storyteller strives to shed light on texts with a visual nature that raises questions about existential, ethical, and aesthetic issues. Methodology: The research is based on the descriptive and analytical approach, examining the photographic implications in the short stories written for children in Iraq in the third millennium and theoretically interpreting it through a vision that centers on the photographic emphasis in presenting all elements of the narrative work.w It conducts a practical study by analyzing it artistically to reveal the extent to which the mechanisms of photography combine with storytelling. Results: The research has yielded significant findings, the most important of which is establishing the link between what is written and photographic to present a vision that stops at transforming storytelling into a text with a hidden function that goes beyond the aesthetic into interactivity. It aims to establish a cultural, intellectual, and psychological, framework that encourages children to observe, and distances them from indoctrination and isolation. Conclusion: The writer of the short story written for children in Iraq in the third millennium sought to employ the capabilities of (the camera lens) by focusing on the capturing the moment realistically. It implies the timeless value within the passage of time, as well as its spatial value from its perspective and various angles, condensing events, in a step to enrich the narrative text.